PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMP SUMBANGSIH - Lidya Lidya (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The process of borrowing and the data recording performed on library books junior's contribution is still not fully computerized, so often finding difficulty in making the report as well as in existing data storage. The problems that exist in the junior's contribution raises the desire to have a new system in the library that can overcome these problems. Then designed a web-based library information system using PHP, MySql, and XAMPP with methods of system development life cycle (SDLC) that is expected to assist in the process of working in a library Junior contribution. The function of the program, among others: students can look at the books and magazines in the library, a member of the library, borrow books via the web, see the list of borrowing and repayment status, f.a.q, critique and suggestions and see the latest news in the library. As for the librarian, this program serves to enter the data of books, magazines of data, managing data members, f.a.q the data, the data criticisms and suggestions, and to report lending, the report returns, and report books and magazines. The purpose and benefits of this design include in order to facilitate student looking for a book in the library, facilitate students in borrowing/restore, encourage students active in the library, and assist librarians in doing his job.